COVID-19’s Influence on Ocular Emergency Visits at a Tertiary Referral Center and Its Relationship to Emergency Indications by the American Academy of Ophthalmology - Sharon Armarnik; Michael Kinori; Amir Abd Elkader; Sharon Blum Meirovitch; Noa Kapelushnik; Shiran Madgar; Hila Goldberg; Oded Sagiv; Tamara Wygnanski-Jaffe; Ayelet Priel (Journal of Ophthalmology)
Purpose. To examine the trends of ocular emergency admissions during the COVID-19 pandemic at a tertiary care center. Methods. The study’s sample consisted of all patients who were seen in the ophthalmic emergency room (OER) between March 15 and April 15, 2020 (during the COVID-19 pandemic) and in the same time frame of the previous year. The cases were categorized as urgent vs. nonurgent according to the AAO urgency guidelines during the coronavirus period, and the ability to treat the case with telemedicine was evaluated retrospectively. Results. A total of 553 patients were admitted to the OER during the pandemic period, whereas in the same time frame of the previous year, 1,069 were admitted. The female/male proportion was 526/543 (49.2%/50.8%) in 2019 and 258/259 (46.7%/53.3%) the following year. Age (years, average ± SD) was 44.7 ± 24.5 in 2019 and 47.9 ± 23.4 in 2020. There were more self-referrals in 2020 compared to 2019 (41.1% vs. 32.6%; p=0.0004). The time spent in the OER was reduced from 109 ± 74 (minutes, average ± SDV) in 2019 to 73 ± 51 in 2020 (p<0.0001). The most common cause of OER examinations in 2020 was related to the posterior segment of the eye (23.9%), whereas infection and inflammation of the anterior segment were the most common causes in 2019 (35.5%). Urgency by AAO standards was in agreement in 26.7% admissions in 2019 and 35.6% in 2020 (p=0.0002). Conclusion. The COVID-19 pandemic has influenced several aspects of the OER, including the number of referrals, type of ophthalmic emergency, the time spent in the OER, and the need for emergent treatment. Our change in the treatment algorithm was in agreement with the AAO recommendations during the pandemic.